Efficient electrocatalytic conversion of CO2 to syngas for the Fischer–Tropsch process using a partially reduced Cu3P nanowire. Issue 33 (10th August 2021) - Chang, Bing; Zhang, Xia-Guang; Min, Zhaojun; Lu, Weiwei; Li, Zhiyong; Qiu, Jikuan; Wang, Huiyong; Fan, Jing; Wang, Jianji
Abstract : A partially reduced cuprous phosphide nanowire with surface phosphorus vacancies supported by copper foam (R-Cu3 P/Cu) was synthesized by a doping-induced strategy, and the R-Cu3 P/Cu shows outstanding activity for CO2 -to-syngas conversion. Abstract : Electrochemical conversion of CO2 into syngas (CO and H2 ) has attracted extensive research studies because it is a promising pathway to produce liquid fuels and industrial chemicals. However, to achieve a high current density at a desired CO/H2 ratio is still a great challenge although it is extremely important in practical applications. In this work, we developed a partially reduced Cu3 P nanowire (R-Cu3 P/Cu) by selective phosphating to catalyze the CO2 -to-syngas conversion. It is found that R-Cu3 P/Cu is highly effective for the conversion with a wide tunable range of the CO/H2 ratio (0.1–2.24) and high faradaic efficiency (FE, >93%). More importantly, this catalyst exhibits a record current density of 115 and 82.9 mA cm −2 at the CO/H2 ratio of 2/5 and 1/2, which are precisely required for Fischer–Tropsch synthesis. Mechanism studies reveal that the effective charge transfer from Cu to P on the partial phosphorus vacancy surface makes Cu3 P nanostructures exhibit remarkable activity and selectivity for CO2 reduction by a diatomic activating bimolecular mechanism.